RESPONSIBILITAS DALAM PENJERATAN ILLEGAL FISHING BERDASARKAN HUKUM INTERNASIONAL - Dzikrina Aulia; Sitti Nabila Yusri Budiman; Tanissa Mayra Tsabitha (LPPM Universitas Ekasakti Padang, 2023)
With the freedom to fish on the high seas according to article 86 of the 1982 law of the sea convention, the availability of high seas fish, especially species that are limited and have long migrations, has continued to decline sharply. This will encourage the international community to find a solution to this problem, not intend to fish illegally in other countries' seas. Illegal fishing or what is also known as illegal fishing is illegal fishing activity, a series of fishing that is not regulated by applicable regulations, there is no report to the fishing agency or institution that is available or authorized. The purpose of the author's research is so that the reader understands, the settlement of marine crimes by enforcement according to UNCLOS. Basic doctrinal legal research based on legal positivism uses an approach of convention regulations with legislation. The result of this research is that illegal fishing enforcement is presented as an activity carried out by the state in the form of international cooperation, countries need to work together to follow rules and agreements, either by themselves or with help from groups working with many countries. They can do things together, such as making sure boats are safe, taking care of living things in the sea, keeping the environment clean, learning about the sea, and using technology.